Lami and the Singing Fish - Mohammed, Hadiza (Kachifo Ltd, 2022)
Lami lives in a fishing village with her single father Baba. On day Baba caught a Fish so he asked Lami to clean it. To Lami's surprise, the Fish began to sing to her and asked her for a favour. In return, the Fish promised to give her the treasures of the river. Lami must decide whether to grant the Fish its request or forgo the treasures of the river...
Keywords: Animal; Juvenile Fiction